2012
DOI: 10.3892/ol.2012.645
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible factor-1α, vascular endothelial growth factor and matrix metalloproteinase-2 in sacral chordomas

Abstract: Abstract. Hypoxia-inducible factor-1α (HIF-1α) has been reported to transactivate the expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-2 (MMP-2), which are frequently overexpressed in numerous types of cancer and are known to be significant regulators of angiogenesis. Few studies have investigated the role of these factors in solid tumors, particularly chordomas, which are rare tumors that are thought to originate from notochordal remnants. To clarify whether HIF-1α is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The mutation had already been reported previously in chordoma and is supposed to be tolerated 13 . According to the literature, VEGF has been shown to be expressed in 77.8% of 28 sacral chordomas 17 , 18 . Akhavan-Sigari et al 2013 19 reported low expression of VEGFR-2 in 145 clivus chordomas, yet high expression of VEGFR-2 was correlated with a poor prognosis in their samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation had already been reported previously in chordoma and is supposed to be tolerated 13 . According to the literature, VEGF has been shown to be expressed in 77.8% of 28 sacral chordomas 17 , 18 . Akhavan-Sigari et al 2013 19 reported low expression of VEGFR-2 in 145 clivus chordomas, yet high expression of VEGFR-2 was correlated with a poor prognosis in their samples.…”
Section: Discussionmentioning
confidence: 99%
“…Chordomas inconstantly express some actionable targets, mainly stem-cell factor receptor (c-KIT), platelet-derived growth factor receptors (PDGFR-α and PDGFR-β), receptor tyrosine-protein kinase erbB-2 (HER2/neu) and epidermal growth factor receptor (EGFR) [ 1 , 6 , 7 ]. Li et al [ 8 ] and Chen et al [ 9 ] found high levels of VEGF expression in 71% (25/35) and 77.8% (28/36) of chordomas, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, under hypoxic conditions, HIF-1α becomes stabilized, translocates to the nucleus, and dimerizes with the aryl hydrocarbon receptor nuclear translocator (ARNT) binding to the HIF-1 consensus sequence to activate hypoxia-inducible genes. Recent studies have reported HIF-1α expression in the majority of chordoma samples examined, correlated with VEGF expression and tumour microvessel density [18] , [71] . While we did not detect the induction of HIF1A gene expression in U-CH1 cells maintained in hypoxia, we detected a significant up-regulation of VEGF-A and GLUT1 gene expression, suggesting increased HIF-1α activity in hypoxia.…”
Section: Discussionmentioning
confidence: 97%
“…For example, under hypoxia prostate cancer cells show increased cell proliferation [15] , and prostate [15] , breast [16] and colon [17] cancer cells display increased migration compared to cells cultured under normoxia. In addition, studies have shown that hypoxia can promote stem and progenitor cell properties in various cancers including glioma, glioblastoma and ovarian cancer [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%